POTENSI WISATA RELIGI SITUS BANTEN LAMA SEBUAH KHAZANAH LOKAL ARSITEKTUR ISLAM BANTEN DALAM MENUNJANG EKONOMI MASYARAKAT DI KECAMATAN KASEMEN KOTA SERANG - Ubay Haki; Diah Permatasari (Jurnal Bina Bangsa Ekonomika, 2023)
Kasemen is the name of a sub-district in Serang City which is known for its religious tourism in Banten. Islamic culture developed in Banten, Jakarta, West Java due to the influence of the Sunan Gunung Djati religious syiar, the founder of the Banten kingdom. Therefore, in Kasemen District there are many heritage sites of the Banten Sultanate, such as mosques, forts, palaces, tombs, towers, petilasan, and bridges. This paper aims to examine the potential of religious tourism of the historical site of Banten Lama as a local treasure of Islamic architecture in generating economic income in Kasemen District. The method taken in writing this article uses a historical method approach that has four stages, namely heuristics, verification, interpretation, and historiography. Data sources are obtained through literature review or literature study. Religious tourism of the Old Banten site has very interesting historical potential, and has archaeological characteristics in the era of growing Islam which has the meaning and values of the conception of the region as a form of local Islamic cultural treasures of Banten, so as to attract pilgrims to come to Kasemen